Comparison of chromosomal status in reserved multiple displacement amplification products of embryos that resulted in miscarriages or live births: a blinded, nonselection case-control study - Guoxia Yang; Yan Xu; Yanhong Zeng; Jing Guo; Jiafu Pan; Canquan Zhou; Yanwen Xu (BMC, 2022)
Abstract Objective To analyze chromosomal status in reserved multiple displacement amplification (MDA) products of embryos that result in miscarriages or live births. Methods Patients who underwent preimplantation genetic testing for monogenic disorders (PGT-Ms) without aneuploidy screening were included. The case group included 28 cycles that resulted in miscarriages. Controls included 56 cycles with live births. Comprehensive chromosomal screening (CCS) using next-generation sequencing (NGS) was performed on reserved MDA products from previous blastocyst trophectoderm biopsies. The incidence and type of chromosomal abnormalities in embryos resulting in miscarriages or live births were analyzed. Results Of 28 embryos resulting in miscarriages in the case group, the rate of chromosomal abnormalities was 53.6%, which was significantly greater than 14.3% for those resulting in live births in control group (P < 0.001). Whole-chromosome aneuploidy was not found in the control group but was noted in 25.0% of embryos in the case group. Although the rates of segmental abnormality and mosaicism were also greater in the case group, no significant differences were detected. One chaotic embryo in the control group progressed to live birth. Conclusion Chromosomal abnormalities were the main reason leading to early pregnancy loss. However, abnormalities, such as segmental aneuploidy and mosaicism, should be managed cautiously, considering their undermined reproductive potential.